2021
DOI: 10.3390/jox11010002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resveratrol on Prostate Cancer through Targeting the Tumor Microenvironment

Abstract: Prostate cancer is one of the most common cancers diagnosed in men in the United States and the second leading cause of cancer-related deaths worldwide. Since over 60% of prostate cancer cases occur in men over 65 years of age, and this population will increase steadily in the coming years, prostate cancer will be a major cancer-related burden in the foreseeable future. Accumulating data from more recent research suggest that the tumor microenvironment (TME) plays a previously unrecognized role in every stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…Along with that, recent studies discuss the effect of natural compounds, not only in prostate-cancer cells but and also in CAFs and osteoblasts. For instance, Pietrovito et al, discovered that cannabinoids act on cancer cells and CAFs at the same time by inhibiting CAF activation [38]; Silk and her colleagues reported that resveratrol downregulates Transforming Growth Factor β (TGFβ) expression while it exerts an antiproliferative and a pro-apoptotic effect in prostate CAFs [37]; and Ma and her collaborators found out that a Chinese natural medicine is able to cause CAF death and to reduce their pro-angiogenic capacity by reducing Vascular Endothelial Growth Factor A (VEGFA) production [39,93]. However, we could not detect any alteration regarding the presence of CAFs and TAMs in vivo due to the small number of infiltrated cells in the tumor stroma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with that, recent studies discuss the effect of natural compounds, not only in prostate-cancer cells but and also in CAFs and osteoblasts. For instance, Pietrovito et al, discovered that cannabinoids act on cancer cells and CAFs at the same time by inhibiting CAF activation [38]; Silk and her colleagues reported that resveratrol downregulates Transforming Growth Factor β (TGFβ) expression while it exerts an antiproliferative and a pro-apoptotic effect in prostate CAFs [37]; and Ma and her collaborators found out that a Chinese natural medicine is able to cause CAF death and to reduce their pro-angiogenic capacity by reducing Vascular Endothelial Growth Factor A (VEGFA) production [39,93]. However, we could not detect any alteration regarding the presence of CAFs and TAMs in vivo due to the small number of infiltrated cells in the tumor stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many of those antitumor effects derive from TME modulation. For instance, resveratrol inhibits CAF differentiation, interrupts communication between tumor cells and TME and reduces TAM polarization to proinflammatory macrophages [37]. Likewise, cannabinoids impair CAF activation [38] and a compound containing Chinese herbs named Ligustilide induces their apoptosis and, therefore, reduces angiogenesis [39].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that resveratrol can reverse multidrug resistance in cancer cells, and when used in combination with clinically used drugs, it can sensitize cancer cells to standard chemotherapeutic agents [27]. There have been many reports that resveratrol can inhibit tumor processes by regulating multiple pathways, and the pathways affected by resveratrol, such as the PI3K pathway, Wnt signaling, and inflammation-related pathways, affect the PRCA immunosuppressive microenvironment [28]; thus, resveratrol could become an adjuvant drug for immunotherapy to help improve its effectiveness. I-BET-762 is also well studied and was reported to reduce MYC expression in PRCA and subsequently inhibit cell growth and reduce the tumor burden [29].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has demonstrated potential anti-cancer activity against several types of human cancer, including prostate ( 27 , 28 ), breast ( 29 , 30 ), colorectal ( 31 , 32 ), and skin cancers ( 33 ), and has also been used as a chemotherapeutic drug to treat various lung cancer cells ( 34 – 36 ). Its anti-lung cancer effect has been widely studied, with results suggesting that it could exert potent anti-tumor effects by upregulating microtubule-associated protein 1 light chain 3 ( 37 ) and p53 ( 38 ), downregulating smad activator 2 and 4 ( 39 ), and inhibiting the phosphatidylinositol-3-kinase pathway ( 40 ).…”
Section: Discussionmentioning
confidence: 99%